SARS-CoV-2 infection prevention and control measures in Belgian schools between December 2020 and June 2021 and their association with seroprevalence: a cross-sectional analysis of a prospective cohort study - Milena Callies; Ines Kabouche; Isabelle Desombere; Joanna Merckx; Mathieu Roelants; Melissa Vermeulen; Els Duysburgh (BMC, 2023)
Abstract Background To protect school-aged children from the potential consequences of a new viral infection, public health authorities recommended to implement infection prevention and control (IPC) measures in school settings. Few studies evaluated the implementation of these measures and their effect on SARS-CoV-2 infection rates among pupils and staff. The aim of this study was to describe the implementation of infection prevention and control (IPC) measures in Belgian schools and assess its relation to the prevalence of anti-SARS-CoV-2 antibodies among pupils and staff. Methods We conducted a prospective cohort study in a representative sample of primary and secondary schools in Belgium between December 2020 and June 2021. The implementation of IPC measures in schools was assessed using a questionnaire. Schools were classified according to their compliance with the implementation of IPC measures as 'poor', 'moderate' or 'thorough'. Saliva samples were collected from pupils and staff to determine the SARS-CoV-2 seroprevalence. To assess the association between the strength of implementation of IPC measures and SARS-CoV-2 seroprevalence among pupils and staff, we conducted a cross-sectional analysis using the data collected in December 2020/January 2021. Results A variety of IPC measures (ventilation, hygiene and physical distancing) was implemented by more than 60% of schools, with most attention placed on hygiene measures. In January 2021, poor implementation of IPC measures was associated with an increase in anti-SARS-CoV-2 antibody prevalence among pupils from 8.6% (95%CI: 4.5 - 16.6) to 16.7% (95%CI: 10.2 - 27.4) and staff from 11.5% (95%CI: 8.1 - 16.4) to 17.6% (95%CI: 11.5 - 27.0). This association was only statistically significant for the assessment of all IPC measures together in the population comprised of pupils and staff. Conclusions Belgian schools were relatively compliant with recommended IPC measures at the school level. Higher SARS-CoV-2 seroprevalence among pupils and staff was found in schools with poor implementation of IPC measures, compared to schools with thorough implementation. Trial registration This trial is registered under the NCT04613817 ClinicalTrials.gov Identifier on November 3, 2020.